Estudo comparativo sobre o projeto estrutural de lajes nervuradas e maciças em concreto armado na situação de incêndio - Oliveira, Guilherme Riquena de (Universidade Federal de São Carlos, 2020)
When compared to solid reinforced concrete slabs, the ribbed slabs are designed in order to make the most efficient use of the qualities existing in the materials that constitute them, through the cover and ribs set, the use of concrete is optimized for compression and the use of steel to withstand the tensile stresses existing in the slabs. Due to this better use of the materials used in the construction of the ribbed slabs, these slabs are considered more economical than the solid ones, this for larger spans (from 6 or 7 meters). However, the mandatory verification of reinforced concrete structures for the fire situation tends to diminish this economic advantage possessed by the ribbed slabs, because when checking a slab to the fire situation, the thermal insulation capacity of this element is also verified. so that minimum thicknesses of concrete slabs are required. Thus, in this work we studied the design of solid and ribbed slabs in reinforced concrete in the fire situation using mostly two standards of the Brazilian Association of Technical Standards (ABNT), ABNT NBR 6118: 2014 - Design of reinforced concrete structures and ABNT NBR 15200: 2012 - Design of reinforced concrete structures in a fire situation with the tabular method. The dimensioning of the structures for different design impositions was carried out with the aid of the CAD / TQS software, and through the iterative process, the dimensions of the slabs were obtained so that the arrows obtained were as close as possible to the maximum arrows of each span. When the slabs were dimensioned and detailed, the quantities of steel and concrete used in the design of each slab were obtained. Thus, through the tables and graphs generated in the Excel software, a comparative study was carried out between the solid and ribbed slabs for different contour situations. (spans, classes of environmental aggressiveness and height of the building). A comparative study between the different construction methods was carried out, the use of solid and ribbed slabs in the structural design was discussed.
Comparative study on the structural design of ribbed and flat slabs in reinforced concrete in fire situation
Keywords: Projeto. Concreto. Armado. Situação. Incêndio. Laje. Maciça. Nervurada. EPS. Comparação. Tabular. Design. Concrete. Reinforced. Situation. Fire. Slab. Flat. Ribbed. EPS. Comparision. Tabular.; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS